In the substitution method, we solve one equation for a variable and then substitute that expression into the other equation. This allows us to solve for the other variable.
In this case, we can solve the first equation for y:
3x + y = 18
y = 18 - 3x
Now, we substitute this expression for y in the second equation:
4x + 2(18 - 3x) = 10
Simplifying this equation, we get:
4x + 36 - 6x = 10
This is the equation that Jasmine should solve in step 3 using the substitution method.
Jasmine decides to solve this system of equations using the substitution method
3x + y = 18
4x + 2y = 10
which equation should be solved in step 3 using jasmines method
1 answer